STUDI KOMPARATIF PENGGUNAAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION DAN PROBLEM BASED LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR TIK SISWA KELAS VIII SMP NEGERI 1 SAWAN - ., Ni Kadek Dwi Juli Lestari; ., Dr. Ketut Agustini, S.Si, M.Si.; ., Gede Saindra Santyadiputra, S.T., M.Cs (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2016)
Penelitian ini bertujuan untuk mengetahui motivasi dan hasil belajar siswa antara siswa yang dibelajarkan dengan model pembelajaran Team Assisted Individualiztion (TAI) dan model pembelajaran Problem Based Learning (PBL). Jenis penelitian ini adalah eksperimen semu atau disebut dengan quasi ekperimen. Dengan rancangan â€œPost Test Only With Non Equivalent Control Group Designâ€. Populasi penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 1 Sawan tahun ajaran 2016/2017 yang berjumlah 333 orang. Sampel diambil dengan teknik simple random sampling. Sampel yang dipilih adalah kelas VIIIC menjadi kelas eksperimen 1 yang dibelajarkan dengan menggunakan model pembelajaran Team Assisted Individualiztion (TAI), VIIID menjadi kelas eksperimen 2 yang dibelajarkan dengan model pembelajaran Problem Based Learning (PBL), dan VIIIB menjadi kelas kontrol yang dibelajarkan dengan model pembelajaran konvensional. Data yang dikumpulkan dalam penelitian ini adalah hasil belajar siswa yang dikumpulkan dengan tes psikomotor dan objektif dimana tes psikomotor berjumlah 5 soal dan tes objektif berjumlah 30 butir soal. Data dianalisis dengan menggunakan statistik deskriptif dan ANOVA. Hasil penelitian menunjukkan bahwa terdapat perbedaan motivasi dan hasil belajar siswa yang signifikan anatara siswa yang belajar menggunakan model pembelajaran TAI, PBL, dan Konvensional dilihat dari nilai rata-rata. Nilai rata-rata kelompok kelas eksperimen TAI yaitu 39,51, nilai rata-rata kelompok eksperimen PBL yaitu 36,21, dan kelompok kelas kontrol adalah 32,29. Hasil belajar siswa yang belajar dengan model Team Assisted Individualiztion (TAI) lebih baik dibandingkan dengan siswa yang belajar menggunakan model pembelajaran Problem Based Learning (PBL), dan siswa yang belajar menggunakan model pembelajaran konvensional yang dilihat dari nilai rata-rata hasil belajar dari diterapkannya ketiga model.Kata Kunci : Study Komparatif, Team Assisted Individualization (TAI), Problem Based Learning (PBL), Motivasi, Hasil Belajar Siswa The purpose of this research was want to know studentsâ€™ motivation and studentsâ€™ learning outcomes which were taught by using Team Assisted Individualization (TAI) and Technique and problem Based Learning (PBL) technique. This research was quasi experimental and the design was â€œPost Test Only with non-Equivalent Control Group Design.â€ The population of this research was all of the students in eight grade of SMP Negeri 1 Sawan in academic year 2016/2017. There are 333 students, then the sample was selected by using simple random sampling technique. There were three class were selected as the sample for this research, which were VIIIC class was selected as experimental 1, who were taught by using Team Assisted Individualization (TAI) Technique, VIIID class as experimental 2, who were taught by using Technique and problem Based Learning (PBL) technique, and VIIIB as control group, who were taught by using conventional technique. The data collected in this research were the studentsâ€™ learning outcomes that was tested by using psychomotor test and objective test. In psychomotor test there was 5 question and in objective test there was 30 items. Data were analyzed by using descriptive statistics and ANOVA. The result of this research was there are significant different on studentsâ€™ outcomes between students who were taught by using Team Assisted Individualization (TAI) technique, Problem Based Learning (PBL) technique and Conventional technique. The studentsâ€™ learning outcomes who were taught by using Team Assisted Individualization (TAI) technique had higher than the students who were taught by using Problem Based Learning (PBL) technique and Conventional technique.Key words: Think Pair Square, Think Pair Share, learning achievement, learning motivation, and student response. The result of the study showed that there was the significant difference of the motivation and learning result of the student between the students that were studied by TAI model, PBL model, and conventional model that has occurred by average of the result. The average result of the class group of TAI model was 39,51, the class group of PBL model was 36,21, and 32,29 for class control of conventional model. The learning result of the students that studied by TAI model was better that the students that studied by PBL model, and the students that studied by conventional learning model through the average of the learning result of the application of the three learning models.keyword : Comparative Study, Team Assisted Individualization (TAI), Problem Based Learning (PBL), Motivation, Studentsâ€™ learning outcomes.